PERANCANGAN DAN IMPLEMENTASI SISTEM PENERJEMAH TEKS BAHASA INGGRIS KE BAHASA BALI DENGAN MENGGUNAKAN PENDEKATAN BERBASIS ATURAN (RULE BASED) - I Putu Deni Pratama; Agus Muliantara (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2012)
Many foreign tourists coming to Bali did not know Balinese language so it was difficult for them to give massages to the Balinese people. One of the solutions to facilitate the tourists was by creating a translating system from English into Balinese language. This study designed the system used to translate texts from English into Balinese language using some input. This web-based designed system used PHP and MySQL as the programming languages. This system which was used to translate English texts into the Balinese ones was implemented using rule-based approach. It implemented four work modules such as scanner, parser, translator, and evaluator. The syntactical rules implemented in this system were context free grammar and MD-DM pattern. The syntactical rule was used to analyze the syntactical structure of input based on grammar. The pattern of MD-DM implemented on the translator’s module functioned to obtain the patterns of words which were available in the Balinese language. 6 experts with 100 sample data in the form of English texts in tourism showed that in general the translation equivalents produced by the system could be understood and that the results were good enough. This could be proved by the average score of precision obtained, that is, 89.3%.